The Effect of Vaginal Administration Isosorbide Mononitrate on Cervical Ripening and Induction of Labor In Postterm Pregnancy - Hamideh Yazdizadeh; Parvin Abedi; Shahnaz Najar; Kambiz Ahmadi; Vahideh Zaker Zakerhoseiyni (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Several findings have shown that Nitric oxide donors can be effective for cervical ripening. The aim of this study was to determine whether Isosorbide mononitrate (IMN) administrated vaginally is effective for cervical ripening and induction of labor in nullipare women at 40 – 42 weeks gestation.Subjects and Methods: A double blind, placebo – controlled, randomized clinical trial was carried out at the Sina hospital in Ahvaz in 2010. Eighty nulliparous women with uncomplicated pregnancy, Cephalic singleton fetus at 40 – 42 weeks of gestation and Bishop score≤ 4 were allocated randomly to receive either Isosorbide mononitrate (2×20 mg) or placebo(2 tablets) vaginally for two doses at least 24 hours before induction of labor with oxytocin. Modified Bishop Score after 24 hours, induction to active phase interval and duration of active phase were evaluated in each group. The data were analyzed using t-test, chi square, Survival Analize(Kaplan Mayer) and Repeated measure in Spss ver 16.0. P- value less than 0.05 were considered as statistically significant. Results: In the IMN group, there was a significant increase in the mean modified Bishop score (p=0/008). Mean duration between induction to active phase of labor was shorter in the intervention group than the control (p= 0/03). Mean duration of active phase was not different in the two groups (p>0/05). No maternal or fetal side effects were registered (p>0/05) expect headache in case group (p<0/001). Conclusion: Vaginal administration Isosorbide mononitrate is probable effective for cervical ripening.